2022
DOI: 10.3389/fspor.2022.875530
|View full text |Cite|
|
Sign up to set email alerts
|

Youth International Experience Is a Limited Predictor of Senior Success in Football: The Relationship Between U17, U19, and U21 Experience and Senior Elite Participation Across Nations and Playing Positions

Abstract: Athlete participation in youth international competitions is often regarded as crucial to the attainment of future success. However, the link between participation and performance in sports at youth levels and senior levels is unclear at best. To understand this relationship better we conducted two studies of male football players. In Study 1, we examined adult performance at the upper levels of football using a factor analysis and identified the characteristics that define what we termed a “Super Elite” level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Studies on male players have showed that practice experience gained from youth international teams is a limited predictor of senior success [ 12 , 13 ]. Indeed, professional academies show a high turnover of youth players [ 15 ], mainly caused by repeated procedures of selection and de-selection throughout childhood, adolescence, and early adulthood [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on male players have showed that practice experience gained from youth international teams is a limited predictor of senior success [ 12 , 13 ]. Indeed, professional academies show a high turnover of youth players [ 15 ], mainly caused by repeated procedures of selection and de-selection throughout childhood, adolescence, and early adulthood [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite more players joining the junior compared to the senior teams, 9–15% of the junior-to-senior transition rate may not represent a good return on investment. Overall, the present findings suggest that youth experience is a limited predictor of senior success [ 12 , 14 16 ] and indicate a high turnover in national youth teams’ rosters [ 18 ]. The combination of the prospective and retrospective analysis showed that the selection strategies adopted at the youth level were linked to the determination of the players’ pool of the senior national teams only from the U19’s selection onwards.…”
Section: Discussionmentioning
confidence: 93%
“…A study on different European countries, including Scandinavian nations (i.e., Denmark, Norway, and Sweden), Belgium, Germany, and Portugal, highlighted that being included in Under 17 (U17) national selection negatively predicted subsequent participation in international football competitions. Also, the relationship between Under 19 (U19) selection and senior international participation was weak and increased with the selection at the Under 21 (U21) level [ 16 ]. Successful transition from youth-to-senior in football can also be measured by the ability of a player to obtain a professional contract in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as performance level, consistency of performance, rate of performance improvement, long-term participation in a youth national team, and resilience to physical and psychological stress have been described in the literature [38,39]. Career progression also appears to be influenced by the relative age effect [40,41]. The relative age effect is the phenomenon that athletes born in the first half of the selection year are overrepresented in professional sports.…”
Section: Impact Of Injury On Career Progressionmentioning
confidence: 99%